The Relationship Between Self-Esteem and Body Image in Chronic Kidney Failure Patients Undergoing Hemodialysis - Alfonsius Ade Wirawan; Gratsia Victoria Fernandez; Stefan Andrew Glorious Kambey (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: Patients undergoing hemodialysis often experience physical changes. These changes can affect their perception of their body image. Self-esteem is believed to be a key determinant of body image. Methods: This was a quantitative study with a cross-sectional design. Measurements were made using the Rosenberg Self-Esteem Scale (RSE) and the Body Image Scale (BIS). The sample size was 78 patients with chronic kidney disease undergoing hemodialysis. Results: The Spearman rank test between self-esteem and body image in patients undergoing hemodialysis showed a p-value of 0.000 (p < 0.05) and an r-value of 0.404, indicating a statistically significant positive correlation between the two variables. Conclusion: There is a significant correlation between self-esteem and body image in patients undergoing hemodialysis